THE INFLUENCE OF ZALORA BRAND AMBASSADOR, PAYMENT CONVENIENCE, AND RETURN POLICY TOWARD E-TRUST AND ITS EFFECT TOWARDS PURCHASE INTENTION - B1024141023, Carin Sanjaya B1024141023 (Jurnal Manajemen Update, 2019)
The large population of Indonesia and increasing internet access and usage provide an ideal environment for a thriving e-commerce scene. With many e-commerce options, we sought to discover whether trust have impact on the purchase intention. Many ways are done by e-commerce companies to increase consumer trust where it is expected that with a large number of e-commerce choices consumers more prefer that company to others. There are many factors that may impact trust but this study focuses primarily on the e-trust that relate to brand ambassador program, payment convenience, and return policy. The purchase intention variables that will be investigated in this paper is interesting because it measures how high the possibility of consumers in buying intention because of the higher e-trust on an e-commerce. In this study, the object that being used is one of the most well-known fashion e-commerce companies in Indonesia which is Zalora Indonesia. This study aims to determine the influence of Zalora brand ambassador, payment convenience, and return policy toward e-trust and its effect towards purchase intention on Zalora Indonesia in Pontianak. The population in this study is customers who know about Zalora Indonesia and have experience in shopping on e-commerce. Data collection method used in this study is by distributing questionnaires and measurements are carried out using a Likert scale. This research was processed using Structural Equation Modeling (SEM) method with Partial Least Square (PLS). SmartPLS 3.2.7 software used to complete the quantitative data. The findings of this study show that return policy has the greatest influence on e-trust which indicates that in order to gain trust from customers, e-businesses must offer an easy return policy. Zalora brand ambassador and payment convenience are also found to have a positive influence toward e-trust. In addition, e-trust has positively influence purchase intention on Zalora Indonesia.Â Keyword: Zalora brand ambassador, payment convenience, return policy, e-trust, purchase intentionÂ REFERENCESBaum, David, 1999. E-Commerce. Oracle Corp. New Jersey.Boswarva, Jessica, 2012. The Marketing Relevance of Australian Cosmetic Brand Ambassadors.Centeno, Clara, 2002. Building Security and Consumer Trust in Internet Payments.Choi, Yongrok and Do Quynh Mai, 2017. The Sustainable Role of the E-Trust in the B2C E-Commerce of Vietnam.Delafrooz, Narges, Laily H. Paim, and Ali Khatibi, 2010. Understanding Consumer's Internet Purchase Intention in Malaysia.Duffy, Dennis L., 2005. Affiliate Marketing and Its Impact on Eâ€commerce.Gregory, Nicholas, Roberto Daniele, and Levent Altinay, 2013. Affiliate Marketing in Tourism: Determinants of Consumer Trust.Gita, Devi and Retno Setyorini, 2016. The Effect of Brand Ambassador to the Brand Image of Online Company from Zalora.co.id.Hong, Ilyoo B., and Hwihyung Cho. The Impact of Consumer Trust on Attitudinal Loyalty and Purchase Intentions in B2C E-Marketplaces: Intermediary Trust vs. Seller Trust. International Journal of Information Management 2011, 31, 469â€“479.Kidane, Teklehaimanot Tadele and R.R.K.Sharma, 2016. Factors Affecting Consumersâ€™ Purchasing Decision through E-Commerce.Kim, S and H. Park, 2013). Effects of Various Characteristics of Social Commerce (S-commerce) on Consumers Trust and Trust Performance. International Journal of Information Management, 33(2), 318â€“332.Loan, Kae Tran My, Benjamin Chan Yin Fah, and Behrang Samadi, Exploring Customer Purchasing Intention over Online Store.Lucouw, L., 2014. The Impact of Brand Ambassador Transgression on Brand Perception.Murphy, Gregory B., 2003. Propensity to Trust, Purchase Experience, and Trusting Beliefs of Unfamiliar E-Commerce Ventures.Putro, Haryo Bismo and Budhi Haryanto. 2015. Factors Affecting Purchase Intention of Online Shopping in Zalora Indonesia, Sebelas Maret University, Surakarta.Rong, Li, Jae Jon Kim, Jae Sung Park, 2007. The Effects of Internet Shoppers' Trust on Their Purchasing Intention in China.Sharma, Bhuvanesh Kumar, Drlokesh Arora, and Dr. Swarna Parmar, 2017. Impact of Trust and Security on Purchase Intention with Reference to Online Purchase through Social Media.Syafaruddin, Suharyono, and Srikandi Kumadji, 2016. The Effect Of Electronic Word Of Mouth Communication On Trust And Purchase Intention As Well Asthe Impact On Purchase Decisions - Survey on Consumer Online Shopping Zafertech.com.Taddeo, Mariarosaria, 2009. Defining Trust and E-trust: Old Theories and New Problems.Virgillo, Di Francesca and Gilda Antonelli, 2017. Consumer Behavior, Trust, and Electronic Word-of-mouth Comunication: Developing an Online Purchase Intention Model.Wang, Miao and Hong Jian Qu, 2017. Review of the Research on the Impact of Online Shopping Return Policy on Consumer Behavior.Wood, S. L. (2001). Remote Purchase Environments: The Influence of Return Policy Leniency on Two-Stage Decision Processes. Journal of Marketing Research, 38(2), 157â€“169.Yan, Wong Tak and Yeung Yuen Ha, 2011. Customers' Trust and Purchase Intention towards Taobao's Alipay - China Online Marketplace (Younus, Sohail, Faiza Rasheed and Anas Zia, S. L., 2015. Identifying the Factors Affecting Customer Purchase Intention.Â Web References:BrandTrust, 2007. Brand Ambassador [online]. Available at: https://www.brand-trust.de/en/glossary/brand-ambassador.php[Accessed on 15th November 2018].Harquin, 2015. From Customers to Brand Ambassadors [online]. Available at: http://www.harquin.com/articles/WCC_BrandAmbssdrSlides_050115.pdf [Accessed on 2nd August 2018].Kompasiana, 2015. Zalora Menjadikan Pelanggan Sebagai Brand Ambassador [online]. Available at: https://www.kompasiana.com/kapitaselektakomunikasi/5665cb9bb37a61eb0bf52a02/zalora-menjadikan-pelanggan-sebagai-brand-ambassador [Accessed on 2nd August 2018].iPrice, 2019. Â Â Â Â  Peta E-commerce Indonesia [online]. Available at: https://iprice.co.id/insights/mapofecommerce [Accessed on 24th January 2019].Securion Pay, 2017. Â Â Â Â  What is an E-payment System? [online]. Available at: https://securionpay.com/blog/e-payment-system/ [Accessed on 2nd August 2018].Â